2016
DOI: 10.1371/journal.pgen.1006353
|View full text |Cite
|
Sign up to set email alerts
|

A Multistate Toggle Switch Defines Fungal Cell Fates and Is Regulated by Synergistic Genetic Cues

Abstract: Heritable epigenetic changes underlie the ability of cells to differentiate into distinct cell types. Here, we demonstrate that the fungal pathogen Candida tropicalis exhibits multipotency, undergoing stochastic and reversible switching between three cellular states. The three cell states exhibit unique cellular morphologies, growth rates, and global gene expression profiles. Genetic analysis identified six transcription factors that play key roles in regulating cell differentiation. In particular, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 89 publications
1
30
0
Order By: Relevance
“…The white-opaque switch is currently thought to have evolved in the ancestor to C. albicans and Candida tropicalis and regulates sexual competency in both extant species (48,49). Given our identification of MAPK signaling differences between C. albicans white and opaque cells, we examined C. tropicalis transcriptome data (50) and found that STE4 was expressed at a twofold higher level in opaque cells than in white cells (SI Appendix, Fig. S7).…”
Section: Discussionmentioning
confidence: 99%
“…The white-opaque switch is currently thought to have evolved in the ancestor to C. albicans and Candida tropicalis and regulates sexual competency in both extant species (48,49). Given our identification of MAPK signaling differences between C. albicans white and opaque cells, we examined C. tropicalis transcriptome data (50) and found that STE4 was expressed at a twofold higher level in opaque cells than in white cells (SI Appendix, Fig. S7).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our data show that in wild-type cells, inhibition of the Ryp pathway by an Msb2-dependent mechanism is likely to be a key step in the switch from yeast to filaments in response to temperature. Notably, in Candida spp , an antagonistic regulatory relationship between Wor1 (an ortholog of the H. capsulatum Ryp1 protein) and Efg1 (an ortholog of the H. capsulatum Stu1 protein) is critical for controlling the switch between distinct developmental states [36, 51–53].…”
Section: Discussionmentioning
confidence: 99%
“…The previously reported white and opaque Tef2-GFP and Tef2-mCherry strains (Takagi et al 2019) are derived from the switching capable AHY135 strain (Hernday et al 2013), where the HIS1 and LEU2 markers were added back to RZY47, itself a sorbose selected a / a copy of the SN87 a /α his1 leu2 strain (Noble and Johnson 2005; Zordan et al 2006). C. albicans clinical isolates L26 and P37005 (Lockhart et al 2002), C. dubliniensis CD36 (Sullivan et al 1995), C. tropicalis MYA3404 (Joly et al 1996), the C. tropicalis AM2005/0093 derived white-opaque switching strains (Anderson et al 2016), and Candida parapsilosis CBS604/ATCC22019 (Guerin et al 1989) have all been previously reported.…”
Section: Methodsmentioning
confidence: 96%